Genetic Polymorphism of TLR-4 and CD-14 in Patients with Chronic Prostatitis - Al-Jobouri, Worood Ali Mukheef; Al-Saadi, Mohammed A. K.; Al-Marzooq, Wadhah Adnan Abbas (Medical Journal of Babylon, 2025)
Abstract Background: Prostatitis is the medical term for inflammation of the tissue in the prostate gland. It is recognized to be associated with innate immunity since several cytokines are implicated in the occurrence and progression of Chronic abacterial prostatitis/chronic pelvic pain syndrome. Objectives: Study the relationship between immune status involving genetic polymorphism for host-microbes interacting receptors and the occurrence of chronic prostatitis (CP). Materials and Methods: This case-control study involved a population of CP patients and healthy individuals. Full information was taken from each subject. A total of 40 samples were collected from patients diagnosed with CP according to their clinical manifestations, with an age range of 17-62 years. Patients were diagnosed by a consultant urologist. A total of 50 venous blood samples were taken from apparently healthy persons to serve as the control group. The study was conducted between December 2022 and June 2023, within the Urology Department and Microbiology Department in the College of Medicine, University of Babylon, and Hilla Teaching Hospital. Results: The mean age of patients with CP was 35.57 ± 8.81 years, while that of control subjects was 33.24 ± 9.55 years. There was no significant difference in mean age between patients with CP and control subjects (P = 0.236). The distribution of TLR4-rs11536889-G/C, TLR4-rs1927911-C/T, CD14-rs5744454-C/A, and CD14-rs2569190-T/C polymorphisms was detected using the Tetra-amplification-refractory mutation system-polymerase chain reaction (ARMS-PCR) technique. Regarding genotype mode, there was a non-significant difference in the frequency distribution of genotypes between patients with CP and healthy controls. Conclusion: The results revealed a significant association between types of infection and results of T-ARMS-PCR (P = 0.022). However, there were no significant differences in the frequency distribution of genotypes of toll-like receptor 4 (TLR-4) and cluster of differentiation 14 (CD-14) between patients with CP and healthy controls. Also, the results indicated a non-significant association between types of infection and gene polymorphism.